Evidence for Internal and External Binding Sites on Human Tear Lipocalin - Gasymov, Oktay K. (2007)
8-anilino-1-naphthalenesulfonic acid (ANS) is widely used as a probe for locating binding sites of proteins. To characterize the binding sites of tear lipocalin (TL), we studied ANS binding to apoTL by steady-state and time-resolved fluorescence. Deconvolution of ANS binding revealed that two lifetime components, 16.99 ns and 2.76 ns at pH 7.3, have dissociation constants of 0.58 μM and 5.7 μM, respectively. At pH 3.0, the lifetime components show decreased affinities with dissociation constants of 2.42 μM and ∼21 μM, respectively. Selective displacement of ANS molecules from the ANS-apoTL complex by stearic acid discriminates the internal and external binding sites. Dependence of the binding affinity on ionic strength under various conditions provides strong evidence that an electrostatic interaction is involved. Time-resolved fluorescence is a promising tool to segregate multiple binding sites of proteins.